A Level Shifted Resonant LED Driver Configuration with Independent Control - Shaik Mohammed Mukassir (International Journal of Intelligent Systems and Applications in Engineering, 2024)
In this research paper, a level shifted two output resonant LED driver using half-bridge configuration with independent control is proposed. Light emitting diode (LED) systems do not operate below their cut-in voltage. In this proposed configuration, two voltage sources which are connected in series via half-bridge series resonant converter are used to power LED lamp. The voltage difference between operating voltage and cut-in voltage of lamp is produced using half-bridge series converter. LC resonant circuit in each half-bridge helps to zero voltage switching. Thus, power dissipation in switching devices is reduced and energy conversion efficiency can be improved. Since, LEDs are current controlled devices, LED lamp has an inductor in series to reduce ripple current. Thus, this configuration does not require electrolytic capacitor, consequently lifespan of proposed converter for LED application increases. Dimming Operation and regulation of current through the lamp operation are provided using Asymmetrical Duty Cycle (ADC) regulation. Mathematical calculations are performed to validate the proposed two output resonant LED driver.